Outcomes after Conversion from Video-Assisted Thoracoscopic Lobectomy to Thoracotomy - Taylor, Marcus; Raj Krishna, Gokul; Rammohan, Kandadai; Fontaine, Eustace; Joshi, Vijay; Grant, Stuart; Granato, Felice (The Thoracic and Cardiovascular Surgeon, 2023)
Background Lung cancer resections are increasingly being performed via video-assisted thoracoscopic surgery (VATS). Conversion to thoracotomy can occur for many reasons and may affect outcomes. The objective of this study was to investigate the impact of VATS conversion on short- and mid-term outcomes and identify reasons for conversion.Methods Consecutive patients undergoing lobectomy for primary non-small cell lung cancer between 2012 and 2019 in a single UK center were included. Primary outcomes were 90-day mortality, intraoperative conversion, and overall survival. Reasons for conversion were defined as bleeding or nonbleeding. Outcomes were compared between groups using univariable analysis. Multivariable logistic regression analysis was performed to identify risk factors for conversion.Results A total of 2,622 patients were included with 20.6% (n = 541) completing surgery via VATS and 79.4% (n = 2,081) via thoracotomy. The rate of completed VATS surgery increased significantly over time (2012: 6.9%, 2019: 55.1%, p < 0.001). Overall conversion rate was 14.3% (n = 90/631) and has reduced significantly over time (p < 0.001). The rate of conversion due to intraoperative bleeding was 31.1% (n = 28/90). Obesity, male sex, and stage III disease were independent risk factors for conversion. The 90-day mortality rate after conversion was not significantly different from the rate for planned thoracotomy (3.3 vs. 3.4%, p = 0.987). There was no significant difference in overall survival between patients experiencing intraoperative conversion and those undergoing planned thoracotomy (p = 0.135).Conclusion This study demonstrates comparable outcomes for patients undergoing conversion from VATS to those undergoing planned surgery via thoracotomy. It remains unclear if reason for conversion is associated with outcomes.
Keywords: thoracoscopy/VATS; lung cancer; treatment; surgery; outcomes